Perceptions And Practices Encouraging Organ Donation Among Doctors in Surat City - Shaishav Panchal; Toral Desai (Medsci Publications, 2011)
This study was carried out among 100 randomly selected medical practitioners reveals that 47% had encouraged their patients to donate organs commonly cornea and kidney (19%). The study brings out their perceptions regarding organ donation, reasons favouring their view for motivating for organ donation and their perceived barriers towards the same. The study also describes the situations when a patient and his relative should be approached for this sensitive topic.